Availability of Phonological Awareness Skills for Third Grade Students (International Journal of Psychosocial Rehabilitation, 2020)
The current research aims to know the availability of phonological awareness skills for third-grade primary school students and its relationship to reading comprehension. The research community consisted of third-grade primary school students in the Babylon Governorate Center who number (1475) students in (20) primary schools. The two researchers chose the research sample (74) of male and female students (5%) of the students’ total research community. To achieve the research goal, the two researchers prepared a test for the five phonemic awareness skills, namely (discrimination, composition, addition, substitution, and deletion), and a second test was also prepared in reading comprehension skills which are (Direct Understanding and Understanding From me, understanding the meaning of the word, arranging the sentence, and understanding the context), to find the relationship between phonological awareness and reading comprehension, the validity and consistency of the research tools were verified, and the two researchers found in the results of their research the presence of phonemic awareness skills in varying proportions among third-grade primary students, and this is what He invites those in primary school to take an interest in them - and the study also demonstrated that there is a positive relationship between Phonological awareness skills and reading comprehension.